Indicators for Bridge Actions Prioritization - Ortiz-Quesada, Giannina (2021)
This article present some of the general results of the Extension Project: Prioritization of Bridge Structures Using Performance Indicators: Pilot Plan Municipality of El Guarco, this project was executed between January 2018 to December 2019, by the Instituto Tecnológico de Costa Rica. The importance of having tools to prioritize the interventions to be carried out on a group of bridges is shown in the article and the methodology used for such prioritization is described. The proposed methodology is based on the use of 3 strategic indicators: BCI, VAM and USO, defined as technical indicators, complementing this calculation with a socioeconomic indicator, to finally have a list of interventions prioritized in a comprehensive way.